General and Specific Problems of the Formation of Intellectual Operations in Younger Schoolchildren with Learning Difficulties - A.I. Andriashina; L.A. Tishina (Клиническая и специальная психология)
The modern system of inclusive education implies equal access to knowledge for all categories of children. Psychological and pedagogical studies show that there is a heterogeneity in the composition of students in terms of the level of mastering academic skills both within the classroom and among students of individual nosological groups. With the similarity of the symptoms of the manifestation of writing disorders in younger schoolchildren, the state of cognitive functions may be different. Understanding these general and specific features is necessary to organize a personalized approach to correction and education of children with impaired development, which determines the relevance of the study. The article presents the results of a research conducted to identify general and specific patterns of intellectual operations formations in younger schoolchildren who have writing disorders. The sample consisted of 3rd grade students with severe speech disorders and mental retardation enrolled in adapted basic education programs. In the structure of the speech therapy conclusion, all children had a violation of writing on the basis of the lack of formation of language analysis and synthesis operations. As a diagnostic technique for studying the specifics of the formation of basic intellectual operations on nonverbal and verbal material, the method “Classification of objects” was selected and adapted. The results allowed us to conclude about qualitative differences in the formation of thinking components in case of writing disorders of a primary and secondary nature.